Thirst for Intention? Grasping a Glass Is a Thirst-Controlled Action - Revol, Patrice; Collette, Sarah; Boulot, Zoe; Foncelle, Alexandre; Niki, Chiharu; Thura, David; Imai, Akila; Jacquin-Courtois, Sophie; Cabanac, Michel; Osiurak, François; Rossetti, Yves (Frontiers in Psychology, 2019)
Every day and every hour, we feel we perform numerous voluntary actions, i.e. actions under the control of our will. Individual’s ability to initiate goal-directed movement is classically described as a hierarchical motor organisation, from an intentional module, mostly considered as a black box, to muscular activity supporting action execution. The general focus is usually set on the triggering of action by intention, which is assumed to be the only entry to the action cascade, rather than on the preceding formation of intentions. If intentions plays a key role in the specification of movement kinematic parameters, it remains largely unknown whether unconscious cognitive processes may also affect action preparation and unfolding. Recently, a seemingly irrelevant variable, thirst, was shown to modulate a simple arbitrary action such as key-pressing (Velling and Aarts, 2011). Thirsty individuals were shown to produce stronger motor inhibition in no-go trials when a glass of water was present. In the present experiment, we intended to explore whether motor inhibition operates not only upstream from the action cascade but may also affect the unfolding of reaching movements, i.e. at a lower-level control. Thirsty vs non thirsty Control subjects were asked to reach and grasp green (go trial) or red glasses (no-go trial) filled with either water or transparent gel wax with a central candlewick. Thirsty subjects were faster to initiate actions towards water glasses. They also exhibited an earlier maximal grip aperture and a global reduction of movement time which was mostly explained by a shortening of deceleration time. The deceleration phase is correlated with individual’s thirst rating. In addition, no-go trial towards a glass of water tended to inhibit the next movement towards a glass filled with gel wax. Thus, our results show that an unintentional influence of an internal state can reorganise voluntary action structure not only at the decision-making level but also at the level of motor control. Although subjects explicitly paid more attention and were more cautious to glasses filled with water, they reported no explicit sensation of an increased urge to grasp it, further suggesting that these effects are controlled by covert mechanisms.